Disparities in Household Waste Management Achievement under Community-Based Total Sanitation Pillar 4 in Samarinda City, 2024 - 2025 - Riana Embun Masiroh; Blego Sedionoto; Riyan Ningsih (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Implementation of Community-Based Total Sanitation (STBM) Pillar 4 in Samarinda shows varied household waste management achievements influenced by demographic and infrastructural conditions. Objective : This study aims to analyze disparities in waste management implementation and provide strategic recommendations to support the National Medium-Term Development Plan (RPJMN) targets. Research Methods/ Implementation Methods : A descriptive quantitative approach using secondary STBM recapitulation data from Samarinda City (2025) and East Kalimantan Province (2024–2025). Disparities were identified through comparative percentage analysis across sub-districts. Results : City-wide performance reached 72%, with substantial differences between sub-districts due to variations in infrastructure capacity, population density, and environmental practices. Conclusion/Lesson Learned : Addressing disparities requires targeted location based interventions, strengthened cross-sector collaboration, and the development of community waste management infrastructure, particularly 3R processing units an